Estimated tissue and blood N2 levels and risk of in vivo bubble formation in deep-, intermediate- and shallow diving toothed whales during exposure to naval sonar - Kvadsheim, Petter H.; Miller, Patrick J.; Tyack, Peter L.; Sivle, Lise L.; Lam, Frans-Peter A.; Fahlman, Andreas (Frontiers in Physiology, 2012)
Naval sonar has been accused of causing whale stranding by a mechanism which involves formation of tissue N2 gas bubbles. Increased tissue and blood N2 levels, and thereby increased decompression sickness (DCS) risk, is thought to result from changes in behavior or physiological responses during diving. Previous theoretical studies have used hypothetical sonar-induced changes in both behavior and physiology to model blood and tissue N2 tension (PN2), but this is the first attempt to estimate the changes during actual behavioral responses to sonar. We used an existing mathematical model to estimate blood and tissue PN2 from dive data recorded from sperm, killer, long-finned pilot, Blainville’s beaked and Cuvier’s beaked whales before and during exposure to Low- (1-2 kHz) and Mid- (2-7 kHz) frequency active sonar. Our objectives were; 1) to determine if differences in dive behavior affects risk of bubble formation, and if 2) behavioral- or 3) physiological responses to sonar are plausible risk factors. Our results suggest that all species have natural high N2 levels, with deep diving generally resulting in higher end-dive PN2 as compared with shallow diving. Sonar exposure caused some changes in dive behavior, but did not lead to any systematic changes in DCS risk beyond the normal risk range of these species. When a hypothetical removal of the normal dive response (bradycardia and peripheral vasoconstriction), was added to the behavioral response during model simulations, this led to an increased variance in the estimated end-dive N2 levels, but still no consistent change of risk. In conclusion, we cannot rule out the possibility that a combination of behavioral and physiological responses to sonar have the potential to alter the blood and tissue end-dive N2 tension to levels which could cause formation of in vivo bubbles, but the actually observed behavioral responses of cetaceans to sonar in our study, do not imply any significantly increased risk.